Vienna-Heiligenstadt, Pfarrplatz - Czoernig-Gobanz, Herta, 1886-1970 (artist):::Creator:::::::::::: (2020)
Hand-colored etching of the view from the Probusgasse to house no. 2 on the Pfarrplatz ("Schloglisches Haus," 66 Am Platz in Beethoven's time), with musical theme from the Eroica Symphony, estate signed. Beethoven lived in this house in the early summer of 1817.